2001
DOI: 10.1159/000047470
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Two Fluoridation Measures on Erosion Progression in Human Enamel and Dentine in vitro

Abstract: The aim of the present study was to evaluate the effect of fluoride on the progression of erosive demineralisation in human enamel and dentine using a cyclic de– and remineralisation model in vitro. The mineral content expressed in micrometres was determined daily by longitudinal microradiography (LMR) and presented as cumulative mineral loss over 5 days. For erosive demineralisation, all samples were immersed in 0.05 M citric acid (pH 2.3) for 6×10 min/day and stored in a remineralisation solution. Fluoridat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
146
0
52

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(219 citation statements)
references
References 26 publications
17
146
0
52
Order By: Relevance
“…The cariostatic effect occurs due to the formation of a calcium fluoride layer (CaF 2 ) which dissolves and releases ions by pH reduction to prevent that the underlying enamel is reached (11). APF 1.23% has a pH of 3.2-3.5, in which a low concentration of hydrogen dissolves the enamel surface to form CaF 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The cariostatic effect occurs due to the formation of a calcium fluoride layer (CaF 2 ) which dissolves and releases ions by pH reduction to prevent that the underlying enamel is reached (11). APF 1.23% has a pH of 3.2-3.5, in which a low concentration of hydrogen dissolves the enamel surface to form CaF 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1,8,10,11,16,23,24 The in situ study design here using two erosive challenges per day (0.65% citric acid, pH 3.6) appears relatively slight but should reflect situations that can occur in patients with incipient erosion (2.7 μm -4.8 μm). [25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 In vitro and in situ studies show that pretreatment of enamel with tin-containing solutions can protect the enamel surface, inhibiting or reducing the erosive effect of acids through the formation of a superficial layer, containing Sn 2 OHPO 4 , Sn 3 F 3 PO 4 , Ca(SnF 3 ) 2 and CaF 2 -like precipitates, with a low dissolution rate. 1,3,4,12,13,24,32 It is believed that the treatment of the substrate with tin containing fluoride solutions favors the tin incorporation, and perhaps also the fluoride incorporation into the underlying enamel tissue, resulting in a broad structurally modified surface region, rich in tin and resistant to erosive acid challenge 28 . In addition, according to Hjortsjo et al 32 , the mechanism by which metal fluorides inhibitdental erosion is at least partially associated with the presence of HF (hydrofluoric acid) molecules that are capable of penetrating into the enamel and possibly form CaF 2 molecules in the inner enamel substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations